FCS‐like zinc finger 6 and 10 repress SnRK1 signalling in Arabidopsis. (23rd March 2018) - Jamsheer K, Muhammed; Sharma, Manvi; Singh, Dhriti; Mannully, Chanchal T.; Jindal, Sunita; Shukla, Brihaspati N.; Laxmi, Ashverya
Summary: SNF1‐related protein kinase 1 (SnRK1) is a central regulator of plant growth during energy starvation. The FCS‐like zinc finger (FLZ) proteins have recently been identified as adaptor proteins which facilitate the interaction of SnRK1 with other proteins. In this study, we found that two starvation‐induced FLZ genes, FLZ6 and FLZ10, work as repressors of SnRK1 signalling. The reduced expression of these genes resulted in an increase in the level of SnRK1α1, which is the major catalytic subunit of SnRK1. This lead to a concomitant increase in phosphorylated protein and SnRK1 activity in the flz6 and flz10 mutants. FLZ6 and FLZ10 specifically interact with SnRK1α subunits in the cytoplasmic foci, which co‐localized with the endoplasmic reticulum. In physiological assays, similar to the SnRK1 α 1 overexpression line, flz mutants showed compromised growth. Further, growth promotion in response to favourable growth conditions was found to be attenuated in the mutants. The enhanced SnRK1 activity in the mutants resulted in a reduction in the level of phosphorylated RIBOSOMAL S6 KINASE and the expression of E2Fa and its targets, indicating that TARGET OF RAPAMYCIN‐dependent promotion of protein synthesis and cell cycle progression is impaired. Taken together, this study uncovers a plant‐specific modulation of SnRK1 signalling. Significance Statement: SnRK1 is a conserved eukaryotic regulator of adaptive responses during energy deficit. This study demonstrates that two starvation‐induced members of plant‐specific FLZ zinc finger proteins interact with SnRK1α1 in the cytoplasmic foci and repress its level.